Job Satisfaction among Iranian Nurses - Gh Mirzabeigi; S Salemi; M Sanjari; F Shirazi; Sh Heidari; S Maleki (Tehran University of Medical Sciences, 2009)
Background & Aim: Health systems are challenging with increased health demands and limited economic status; whilst, nurses shortages is a worldwide issue. Job dissatisfaction among nurses is a main cause for work leaves. The aim of this study was to assess job satisfaction among Iranian nurses and its related factors. Methods & Materials: In this cross-sectional study, 1058 nurses were selected randomly during 1384-5. A two-sectioned self-report questionnaire was used which included demographic data and job satisfaction scale. Data were analyzed in SPSS version 12.0. Results: Findings showed that only about one third of nurses were satisfied (satisfied & very satisfied) with their jobs (34.30%). In this study, main factors of job satisfaction were job safety (44.5%) as well as working environment and facilities (44.26%). On the other hand, nurses were dissatisfied with their job because of the described job duties (74.75%), managers' way of communication (70%), and their social position (70.3%). Conclusion: Increasing the salary and payment, job equity, modifying working time and shift plans, providing opportunities for the nurses to further their carriers, and continuing education are important issues in increasing job satisfaction.   Key words: nursing profession, job satisfaction, nurs